New Lymantriidae record for Peninsular Malaysia: Toxoproctis hemibathes (Swinhoe) - Norela Sulaiman,; Mohd Faizal Rus Rzerli,; Maimon Abdullah, (Universiti Kebangsaan Malaysia, 2011)
This paper reports on a new record of the itch moth from the family Lymantriidae, Toxoproctis hemibathes (Swinhoe), for Peninsular Malaysia. The islands of Sumatera and Borneo are known to be within the geographical range of Lymantriidae, their habitat preference being the wetland and coastal forests. Our study showed that this species can also erupt in large numbers in specific locations in the southern parts of Peninsular Malaysia and thus, our finding is considered a new record for T. hemibathes (Swinhoe). This specimens were collected using portable ultra violet (UV) light trap during a population outbreak of this species in the Labis District of Johore